Inovasi Strategi Pembelajaran Bahasa Arab Berbasis Keterampilan Komunikatif - Andi Nurul Hidayatullah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses the innovation of Arabic language learning strategies based on communicative skills that emphasizes mastery of four main aspects, namely listening (istima'), speaking (kalam), reading (qira'ah), and writing (kitabah). The background of the research departs from the problem that Arabic language learning in many educational institutions is still dominated by traditional approaches that focus on memorization and translation. As a result, students have difficulty in applying Arabic actively and communicatively. This research aims to describe the concept of language skills-based learning, identify effective methods, and analyze obstacles and implementable solutions. Using a qualitative approach with descriptive methods through literature studies, observations, and interviews, this study found that language skills-based approaches are more effective in improving communication skills than traditional methods. Methods such as Direct Method, Communicative Approach, Audio-Lingual Method, and Total Physical Response (TPR) have been proven to be able to increase students' participation and language competence. In addition, the use of digital media and interactive applications strengthens the learning process. However, limited resources, lack of interactive media, and lack of practice time are major challenges. This study concludes that technology integration, improving educator competencies, and preparing a practice-based curriculum are the keys to the success of Arabic language learning that is communicative and relevant to the needs of the modern era.